ANALISIS PENGARUH KUALITAS PELAYANAN DAN BRAND IMAGE TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS NASABAH (Studi Pada PT Panin Bank KCU Pontianak) - B31111028, RONY GUNAWAN (Jurnal Manajemen Update, 2016)
This study entitled,"Analysis of Service Quality and Brand Image Effect Satisfaction and Its Impact on Customer Loyalty (study at Panin Bank KCU Pontianak)". Â The purpose of this study was a). To determine the effect of service quality on customer satisfaction. b). To determine the effect of brand image on customer satisfaction. c). To determine the effect of service quality on loyalty. d). To determine the effect of brand image on customer loyalty. e). To determine the effect of satisfaction on customer loyalty. f). To determine the effect of service quality on customer loyalty through satisfaction. g) To determine the influence of brand image on loyalty through satisfaction. This research method uses analytics. The population of 100 people. In this study using quantitative analysis using path analysis and hypothesis testing, to test the independent variable on the dependent variable. From the analysis of respondents that service quality, brand image, customer satisfaction and loyalty are in the average value of both categories. This suggests that the relationship of the four variables in this study the effect interconnected. From the test results of the coefficient of determination, quality of service (X1) and brand image (X2) the satisfaction (Y1) and loyalty (Y2), when the value of the coefficient of determination is close to 1 then the variable quality of service (X1) and brand image (X2) the stronger influence in explaining the effect of the satisfaction variables (Y1) and loyalty (Y2). Keywords : Service Quality, Brand Image, Satisfaction, Loyalty